2021
DOI: 10.1177/10963480211014944
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cultural Differences in Customer Retention: Evidence from the High-Contact Service Industry

Abstract: Current tourism landscape and dynamism of the business environment have increased market competitiveness in the high-contact service industry. Hotel operators must now pay greater heed to customer retention by exploring ways to improve customer engagement and experience. Toward this end, this study aimed to examine the interplays between relationship marketing, perceived service quality, corporate image, customer satisfaction, and customer loyalty, as well as the moderating effect of cultural difference betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 99 publications
0
19
0
Order By: Relevance
“…Zeithaml et al (1996) further added that customer satisfaction with products/services often depends on the capability of businesses to meet consumers' needs and expectations; specifically, customers tend to be satisfied with a product/service if the experience of using it exceeds their expectation. Similar to retail consumers, satisfaction is regarded as a key area of business sustainability in the tourism industry, as it can influence tourists' choice of destination as well as their product/service consumption at the destination (Fam et al, 2021;Lee et al, 2011a, b). Prior literature has observed that tourists' destination image is a direct antecedent of their overall satisfaction (Prayag et al, 2017).…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Zeithaml et al (1996) further added that customer satisfaction with products/services often depends on the capability of businesses to meet consumers' needs and expectations; specifically, customers tend to be satisfied with a product/service if the experience of using it exceeds their expectation. Similar to retail consumers, satisfaction is regarded as a key area of business sustainability in the tourism industry, as it can influence tourists' choice of destination as well as their product/service consumption at the destination (Fam et al, 2021;Lee et al, 2011a, b). Prior literature has observed that tourists' destination image is a direct antecedent of their overall satisfaction (Prayag et al, 2017).…”
Section: 3mentioning
confidence: 99%
“…Similar to retail consumers, satisfaction is regarded as a key area of business sustainability in the tourism industry, as it can influence tourists' choice of destination as well as their product/service consumption at the destination (Fam et al. , 2021; Lee et al.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Hence, although service quality is indeed an important aspect in attracting clients, most online travel agencies fail to provide it. This has been suggested by previous studies which found differences between developed and developing countries in terms of customer satisfaction and service quality, in which most Asians have lower standards in evaluating service quality, as found by (Fam et al, 2021;Hussain et al, 2018;Kumarasinghe et al, 2019;Shin & Nicolau, 2022;Tsiotsou, 2019). They also mentioned that the culture of customers influences their expectations of service quality and that most online travel agencies' efforts to improve customer service have failed.…”
Section: If3mentioning
confidence: 70%
“…Several recent studies have touched upon CE in different contexts. In the service industry, a study (Fam et al, 2021) highlighted that the cultural differences between Asian and Western tourists impacted their satisfaction and loyalty. Personal factors and engagement were posited as possible reasons for this disparity.…”
Section: Introductionmentioning
confidence: 99%